Altered Expression of Chemosensory and Odorant Binding Proteins in Response to Fungal Infection in the Red Imported Fire Ant, Solenopsis invicta - Wei, Zhang; Ortiz-Urquiza, Almudena; Keyhani, Nemat O. (Frontiers in Physiology, 2021)
Social insects have evolved acute mechanisms for sensing and mitigating the spread of microbial pathogens within their communities that include complex behaviors such as grooming and sanitation. Chemical sensing involves detection and transport of olfactory and other chemicals that are mediated by at least two distinct classes of small molecular weight soluble proteins known as chemosensory- and odorant binding proteins (CSPs and OBPs, respectively) that exist as protein families in all insects. However, to date, a systematic examination of the expression of these genes involved in olfactory and other pathways to microbial infection has yet to be reported. The red important fire ant, Solenopsis invicta, is one of the most successful invasive organisms on our planet. Here we examined the temporal gene expression profiles of a suite of S. invicta CSPs (SiCSPs1-22) and OBPs (SiOBPs1-16) in response to infection by the broad host range fungal insect pathogen, Beauveria bassiana. Our data show that within 24 h post-infection, i.e. before the fungus has penetrated the host cuticle, the expression of SiCSPs and SiOBPs is altered (mainly increased compared to uninfected controls), followed by suppression of SiCSP and select SiOBP expression 48 h post-infection and mixed responses at 72 h post-infection. A smaller group of SiBOPs, however, appeared to respond to fungal infection, with expression of SiOBP15 consistently higher during fungal infection over the time course examined. These data indicate dynamic gene expression responses of CSPs and OBPs to fungal infection that provide clues to mechanisms that might mediate detection of microbial pathogens, triggering grooming and nest sanitation.